A numerical comparison between ideal and dense gas flow structures in the supersonic regime for a cascade of wedge-shaped straight plates. (5th June 2018) - Nili-Ahmadabadi, Mahdi; Nematollahi, Omid; Cho, Dae Seung; Kim, Kyung Chun
Highlights: Flow passing through a cascade has numerically simulated. Simple straight blades with keen edges are considered. Ideal gas (air) and R245fa gas in a supersonic flow regime are compared. Oblique shock is created in dense gas while a bow shock is in ideal gas. Abstract: A real dense gas such as R245fa is mostly used in organic-Rankine-cycle turbine expanders. The dense gas effects should be taken into account, especially in the transonic and supersonic flow regimes. Oblique shock and the interaction of shock and separation on the turbine blades are phenomena that have little deviation between a real gas and an ideal gas. This research numerically simulated the flow passing through a cascade of simple straight blades with keen edges considered for an ideal gas (air) and dense R245fa gas in a supersonic flow regime. The blade geometry was selected so that the deviations between the dense and ideal gas flows would be clearer than that with actual blades. The AUSM density-based method and NIST real gas model were used to model the ideal and dense gas, respectively. A second-order scheme was used for discretization, and the shear stress transport (SST) model was for the turbulence. The results show that an oblique shock is created on the leading edge when the inlet Mach number is 2.18 in dense gas. In ideal gas, a bow shock is created at the front of the leading edge. Moreover, for a wall pressure coefficient distribution, the separation point in dense gas is posterior than that in ideal gas.